Preembolization functional evaluation in brain arteriovenous malformations: the superselective Amytal test. - Rauch, R A; Vinuela, F; Dion, J; Duckwiler, G; Amos, E C; Jordan, S E; Martin, N; Jensen, M E; Bentson, J; Thibault, L (American Journal of Neuroradiology, 1992)
PURPOSE To describe our experience with the use of Amytal injected through a superselective catheter prior to planned embolization of cerebral arteriovenous malformations.MATERIALS AND METHODS 109 superselective tests were performed with 30-mg injections of Amytal. All patients were evaluated by both clinical examination and EEG.RESULTS Twenty-three of these tests were positive. There were no prolonged neurologic complications of the Amytal test. We also examined the value of EEG monitoring compared to clinical monitoring during the Amytal test. Of the 23 positive Amytal tests, only 12 showed a change on clinical exam (52%). This meant that almost half of the positive Amytal tests would have been falsely called negative (false negative rate of 10%). There were also three positive Amytal tests with changes on clinical examination without any change on EEG.CONCLUSION The superselective Amytal test can be done safely as part of the interventional neuroradiologic procedure. Clinical and EEG monitoring of the patient are essential.